Peran Trait Mindfulness terhadap Stres Kehamilan - Alifa Rizki Chandra; Zulfa Febriani (Lembaga Penelitian Universitas YARSI, 2018)
Pregnancy and giving birth are special moment in women’s life. Pregnancy starts with a dynamic growing period and significant development both physical and mental. Women’s judgement on her pregnancy can determine whether it can be a stressful or not. Trait mindfulness (observing, describing, acting with with awareness, non-judging, nonreactivity) could affect someone on perceiving all accepting daily experience. Trait mindfulness related to mental health. Islam also suggest people to tafakur (contemplate). The study aimed to determine how the role of trait mindfulness take part in a pregnancy stress. The sample was 223 pregnant woman and was taken by accidental sampling technique. This research use Five Facet Mindfulness Questionnaire (FFMQ) Indonesian Version and Pregnancy Experiences Scale – Brief Version (PES-Brief) Indonesian Version as measuring instrument. The result of regression test showed that trait mindfulness on the dimention of acting with awareness predicted 7.3% (R-Square value 0.073, F value 3.439, p value 0,005) the pregnancy stress. However on the dimention of observing, describing, non-judging and non-reactivitydid not has role in the pregnancy stress.